Identifikasi Siswa Berkebutuhan Khusus dan Rancangan Intervensi Melalui Asesmen Psikologi di Sekolah Inklusi - Asri, Dahlia Novarianing; Trisnani, Rischa Pramudia (Universitas Muria Kudus, 2023)
The purpose of this study is to identify students with special needs and design intervention through psychological assessment in inclusive schools. The research was conducted in SDN Sukowinangun 2, Magetan Regency, East Java Province. This research uses a descriptive qualitative approach with psychological assessment consisted of CPM and WISC intelligence tests, documentation, passive role observation, and in-depth interviews as data collection methods. The data sources of this study are informants, events or student interaction activities at school, and documents of students’ backgrounds and other related documents. The subjects of this study were 26 students with special needs. The data were then analized using an interactive analysis model. The results showed that there are 10 developmental disorders found on students with special needs namely slow learning disorders, social disorders, attention deficit and hyperactivity disorders (ADHD), communication development disorders, motor coordination development disorders, hearing loss, slow learning and impairments behaviour, Down syndrome, autism, and vision problems. Slow learning is the most common disorder experienced by students with special needs. Based on the identification of developmental disorders, then an intervention design is prepared, especially in terms of the learning strategy aspects.